Association between frequency of powdered detergent use and irritant contact dermatitis among laundry workers - Eva Nadia Risdiyanti; Resati Nando Panonsih; Arti Febriyani Hutasuhut; Arif Effendi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2026)
Background: Irritant contact dermatitis (ICD) is a non-allergic inflammatory skin reaction caused by direct exposure to irritants. Laundry workers are vulnerable because repeated wet work and detergent contact can disrupt the skin barrier. Purpose: To examine the association between powdered detergent use frequency and ICD among laundry workers. Method: This cross-sectional analytic study included all 60 laundry workers in the study population in Tulang Bawang Barat Regency, Lampung Province, in January 2026. Data were collected using a questionnaire, clinical history taking, and physical skin examination. Categorical data were summarized as frequencies and percentages, and the chi-square test assessed the association between powdered detergent use frequency and ICD. Results: High-frequency powdered detergent use was reported by 26 workers (43.3%), while 17 (28.3%) reported moderate use and 17 (28.3%) reported low use. ICD was identified in 42 workers (70.0%). Powdered detergent use frequency was significantly associated with ICD (p = 0.004). Conclusion: Powdered detergent use frequency was associated with ICD among laundry workers. Because the study was cross-sectional, the finding should be interpreted as an association rather than evidence of causation.